The influence of a static magnetic field on the behavior of a quantum mechanical model of matter. (January 2017) - Vlachova Hutova, E.; Bartusek, K.; Dohnal, P.; Fiala, P.
Highlights: Experimental measurement of a material inserted in various types of magnetic field. Derivation and testing of relatively moving systems. Demonstration that the influence of such motion on a superposed electromagnetic field manifests itself already at relative motion speeds. Testing of the corresponding model based on an electromagnetic field, with description via Maxwell's equations. Presentation of experiments focused on the growth properties of simple biological samples in pre-set external magnetic fields. Abstract: The paper presents an experimental measurement of a material inserted in various types of magnetic field. The related model accepts the time component of an electromagnetic field from the perspective of the properties of matter. Relatively moving systems were derived and tested (Fiala et al., 2011[1] ), and the influence of the motion on a superposed electromagnetic field was proved to exist already at relative motion speeds. In micro- and nanoscopic objects, such as the basic elements of matter, the effect of an external magnetic field on the growth and behavior of the matter system needs to be evaluated. We tested the model based on electromagnetic field description via Maxwell's equations, and we also extended the monitored quantities to include various flux densities. Experiments were conducted with growth properties of simple biological samples in pre-set external magnetic fields.